The Current Status and Influencing Factors of Clinical Inertia in Type 2 Diabetes Patients in Community - LI Dianjiang, PAN Enchun, SUN Zhongming, WEN Jinbo, WANG Miaomiao, WU Ming, SHEN Chong (Zhongguo quanke yixue, 2023)
Background Although type 2 diabetes mellitus (T2DM) cannot be completely cured, however, there is a consensus that timely community management of T2DM patients following guidelines can lead to good glycemic control. However, blood glucose of the patients is chronically suboptimal due to T2DM-related clinical inertia. It is crucial for improving the effectiveness of diabetes control to determine the current status and influencing factors of clinical inertia in T2DM patients in community, but there is limited literature on this topic. Objective To investigate current status and influencing factors of clinical inertia during health management in T2DM patients in community. Methods From January to December 2020, T2DM patients receiving health management services from the national basic public health services in Qingjiangpu and Huaian Districts, Huaian City, Jiangsu Province, were recruited using cluster random sampling method to perform face-to-face questionnaire survey, physical examination, and laboratory tests. Clinical inertia was defined as the absence of intensification in antidiabetic treatment for patients with inadequate HbA1c control (HbA1c≥7.0%) in the past three months. Stepwise multiple Logistic regression analysis was performed to identify influencing factors of the detection of clinical inertia in T2DM patients in community. Results A total of 3 346 T2DM patients with inadequate glycemic control (HbA1c≥7.0%) were included in the study, with the overall detection rate of clinical inertia in T2DM patients of 93.96% (3 144/3 346), 94.84% (1 139/1 201) in men and 93.47% (2 005/2 145) in women, respectively. There were significant differences in the detection rate of clinical inertia among T2DM patients with different levels of dietary control, physical activity, blood glucose monitoring periods, diabetic complications, dyslipidemia (history), and history of coronary heart disease, stroke, and cancer. Stepwise multiple Logistic regression analysis showed that dietary control〔OR (95%CI) =0.585 (0.382, 0.894) 〕, glucose monitoring period≤1 week〔OR (95%CI) =0.470 (0.344, 0.644) 〕, presence of diabetic complications〔OR (95%CI) =0.606 (0.423, 0.868) 〕, dyslipidemia (history) 〔OR (95%CI) =0.725 (0.532, 0.988) 〕, history of coronary artery disease〔OR (95%CI) =0.659 (0.458, 0.949) 〕, and stroke〔OR (95%CI) =0.699 (0.511, 0.955) 〕were associated with a lower prevalence of clinical inertia in T2DM patients (P<0.05) . Conclusion There is a serious problem of clinical inertia in T2DM patients undergoing health management in community, the prevalence of clinical inertia is closely related to patients' dietary control, glucose monitoring period, presence of diabetic complications, and comorbid diseases (history) .